Characterization and speculations on the urbanization of visceral leishmaniasis in Brazil Caracterização e especulações acerca da urbanização da leishmaniose visceral no Brasil - Carlos Henrique Nery Costa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
The available hypotheses or explanations for the urbanization of American visceral leishmaniasis are insufficient. An alternative hypothesis is that changes in the ecology and biology of the vector, Lutzomyia longipalpis, might explain all the new urban epidemiological features of the disease. To tackle the knowledge gaps in this process, certain key research areas need to be prioritized: the role of dogs in expanding transmission in cities, community trials to evaluate new insecticides, and research on the ecological and molecular determinants of Leishmania chagasi transmission. Investment of public funds should focus on the development of a human vaccine, since such a vaccine now appears to be within reach. Even small effects from a vaccine could substantially reduce the impact of the disease, which in the last quarter century has challenged and defeated both the scientific community and the public health field around the world. As hipóteses ou explicações apresentadas até o momento para o processo de urbanização da leishmaniose visceral americana são insatisfatórias. Uma hipótese alternativa é a de que mudanças na ecologia e biologia do vetor, Lutzomyia longipalpis, poderiam explicar as feições epidemiológicas urbanas da doença. De forma a suprir lacunas no conhecimento sobre esse processo de urbanização, destacam-se algumas linhas de pesquisa prioritárias: a investigação do papel de cães na amplificação da transmissão da doença nas cidades, ensaios de campo com novos inseticidas, investigação dos determinantes ecológicos ou moleculares que participam da transmissão de Leishmania chagasi. Esforços com investimentos públicos devem ser feitos para o desenvolvimento de vacinas para humanos, pois uma vacina não parece estar tão distante. Resultados vacinais mesmo modestos podem reduzir substancialmente o impacto dessa doença que, no último quarto de século, desafiou e venceu a ciência e a saúde pública mundo afora.